La definición lexicográfica del vocabulario de germanía y jergal - Lara, Luis Fernando (2012)
In this text, which was originally lectured in the V Coloquio Costarricense de Lexicografía, several of the main topics and limitations proper to the lexicographic definition of criminal slang and jargon vocabulary in general are studied. In the first part, it is argued that the particular character of criminal slang, as guild vocabulary typical of habitual criminals (as thieves or burglars), explains the difficulty to get large and plenty of corpora that would allow a meticulous semantic analysis of the words exclusive of this kind of jargon. The proper usage marks as well as contextual examples are presented as lexicographic resources that although palliative seem to be better than the simple definition with synonyms; this is due to the theoretical problems associated with the synonymy concept (in strict sense). In a second stage, the topic is extended to the issues of the jargon vocabulary definition in general. In this case, the discussion is around the need to make an adequate distinction between technical terms of a specific field and the jargon of other activities related to this field, mainly when we deal with words that point at the same referent (referential synonymy). Again usage marks and well selected examples are shown as useful tools to guide the correct interpretation.